Effect of topically applied Saccharomyces boulardii on the healing of acute porcine wounds: a preliminary study. (December 2016) - Partlow, Jessica; Blikslager, Anthony; Matthews, Charles; Law, Mac; Daniels, Joshua; Baker, Rose; Labens, Raphael
Abstract Background Normal wound healing progresses through a series of interdependent physiological events: inflammation, angiogenesis, re-epithelialization, granulation tissue formation and extracellular matrix remodeling. Alterations in this process as well as the bacterial type and load on a wound may alter the wound healing rate. The purpose of this study was to evaluate the effect of topicalSaccharomyces boulardii on the healing of acute cutaneous wounds, using a prospective, controlled, experimental study, with six purpose bred landrace pigs. Results All wounds healed without apparent complications. Comparison of the mean 3D and 2D wound surface area measurements showed no significant difference between treatment groups as wounds decreased similarly in size over the duration of the study. A significant reduction in wound surface area was identified sooner using 3D assessments (by day 9) compared to 2D assessments (by day 12) (P < 0.001). There was no significant effect of treatment group on the number of multiple isolates or the most common isolates obtained relative to control wounds. There was no histologically appreciable difference between the wounds of the different groups. Conclusions Topical application ofSaccharomyces boulardii does not hasten wound healing or change the wounds' microbiome under the conditions reported in this study.